Kompetensi, Kompleksitas Tugas, Stress Kerja dan Kinerja Auditor BPK RI Perwakilan Provinsi Bali - Krisnanda Adhitama, Sang Putu; Ramantha, I Wayan (E-Jurnal Akuntansi, 2023)
Auditor performance is the activity of carrying out audit tasks that have been completed by the auditor within the specified time period. The aim of this research is to determine the influence of competency, task complexity and work stress on auditor performance. This research was conducted at the BPK Bali Office. The sampling technique used was purposive sampling and the number of samples obtained was 60 respondents. This study uses multiple linear regression analysis. The research results show that competence has a positive effect on auditor performance, while the research results of task complexity and work stress have a negative effect on auditor performance, because BPK Bali auditors clearly know the tasks they are carrying out on the basis of competence and do not experience difficulties or work stress in carrying out their duties. Keywords: Competence; task complexity; work stress; audit performance